Pola Diagnosa dan Rujukan di Fasilitas Kesehatan Tingkat Pertama Swasta X Kota Salatiga - Arlina Safitri; Salsabila Rizki Zulfiandini; Widya Mi’ra Handayani; Anita Kumalahati (SEHATI: Jurnal Kesehatan, 2026)
Referral is a process involving the transfer of authority and responsibility for public health services and disease management between healthcare facilities, both vertically and horizontally. In Indonesia, the healthcare delivery system is organized in a tiered structure, beginning with primary healthcare services provided by first-level healthcare facilities. Secondary healthcare services can only be accessed through referrals from primary healthcare facilities. Tertiary healthcare services are provided based on referrals from secondary or primary healthcare facilities, except in emergency situations